(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the diagnostic accuracy of E-cadherin expression for diagnosis of endometrioid carcinoma in females with abnormal uterine bleeding taking histopathology as gold standard Study Design: Cross sectional validation study. Place and Duration of Study: This study was conducted at the Pathology Department at the Pakistan Institute of Medical Sciences in Islamabad from February to July, 2016. Materials and Methods: Patients were selected using a non-probabilistic, consecutive sampling method. To examine their morphology, the specimens were grossly examined after being fixed in 10% buffered formalin and stained with Hematoxylin and Eosin. E-cadherin staining was evaluated by immunohistochemistry and categorized as "positive" or "negative." Results of E-cadherin and histopathology were compared. Results: In our study the mean age of the patients was 55.31±9.023 years. The E- cadherin diagnoses positive endometrial cancer in 183(77.9%) patients and the histopathology diagnoses positive endometrial cancer in 144(61.28%) patients. the sensitivity of E-cadherin for diagnosing endometrial cancer was 81.94%, specificity was 28.57% and the diagnostic accuracy was 61.28%. Conclusion: According to our study results E-cadherin expression is good and reliable test for diagnosis of endometrioid carcinoma in females with abnormal uterine bleeding taking histopathology as gold standard.